The curse of cash : how large-denomination bills aid crime and tax evasion and constrain monetary policy - Rogoff, Kenneth S., 1953- (Princeton University Press, 2017)
From the New York Times bestselling author of This Time Is Different, “a fascinating and important book” (Ben Bernanke) about the surprising reasons why paper money lies at the heart of many of the world’s most difficult problemsThe world is drowning in cash - and it’s making us poorer and less safe. In The Curse of Cash, acclaimed economist Kenneth Rogoff explores the past, present, and future of currency, from ancient China to today’s cryptocurrencies, showing why, contrary to conventional economic wisdom, paper money surprisingly lies at the heart of some of the world’s most difficult problems.Cash is becoming increasingly marginalized in the legal economy, but there is a record amount of it in circulation -